REAKSI PASAR PADA PENGUMUMAN PRESIDEN DAN WAKIL PRESIDEN REPUBLIK INDONESIA TAHUN 2014 - Zukri, Melli; Husaini, Husaini; Puspita, Lisa Martiah N (JURNAL FAIRNESS, 2016)
The purpose of this study is to examine whether president and vice president events of the Constitutional Court's verdict on the winner of the presidential election in 2014 influence the Indonesian capital market activities.The sample of this study is The Indonesian stock exchange listed companies that classified as LQ45 companies. The analysis used one simple t-test, and one way anova.These results indicate that (1) there is not significant abnormal return and trading volume activity are significantly around the events for all companies listed on the LQ-45 (2) there is no difference abnormal return and trading volume activity significantly around the occurrence of events verdict announcement by the president and vice president of the Constitutional Court on the supporting company Joko Widodo, Prabowo and neutral. The average abnormal return as a whole, before and after the event is negative. While positive only when the incident occurred. While on the average trading volume as a whole, before and after the event is negative.